Computational intelligence based design of biomaterials - Vinoth, Arulraj; Datta, Shubhabrata (Wydawnictwa AGH, 2022)
This paper presents an overview of the applications of computational intelligence techniques, viz. artificial neural networks, fuzzy inference systems, and genetic algorithms, for the design of biomaterials with improved performance. These techniques are basically used for developing data-driven models and for optimization. The paper introduces the domain of biomaterials and how they can be designed using computational intelligence techniques. Then a brief description of the tools is made, followed by the applications of the tools in various domains of biomaterials. The applications range in all classes of materials ranging from alloys to composites. There are examples of applications for the surface treatment of biomaterials, materials for drug delivery systems, materials for scaffolds and even in implant design. It is found the tools can be effectively used for designing new and improved biomaterials.
Computer Methods in Materials Science
Bibliogr. s. 255-[262].
Keywords: biomaterials; design; modeling; optimization; computational intelligence